Experimental validation of multiphase flow models and testing of multiphase flow meters: A critical review of flow loops worldwide - Bello, O. O.; Falcone, Gioia; Teodoriu, C. (WIT Press (Wessex Institute of Technology), 2016)
Around the world, research into multiphase flow is performed by scientists with hugely diverse backgrounds: physicists, mathematicians and engineers from mechanical, nuclear, chemical, civil, petroleum, environmental and aerospace disciplines. Multiphase flow models are required to investigate the co-current or counter-current flow of different fluid phases under a wide range of pressure and temperature conditions and in several different configurations. To compliment this theoretical effort, measurements at controlled experimental conditions are required to verify multiphase flow models and assess their range of applicability, which has given rise to a large number of multiphase flow loops around the world. These flow loops are also used intensively to test and validate multiphase flow meters, which are devices for the in-line measurement of multiphase flow streams without separation of the phases. However, there are numerous multiphase flow varieties due to differences in pressure and temperature, fluids, flow regimes, pipe geometry, inclination and diameter, so a flow loop cannot represent all possible situations. Even when experiments in a given flow loop are believed to be sufficiently exhaustive for a specific study area, the real conditions encountered in the field tend to be very different from those recreated in the research facility. This paper presents a critical review of multiphase flow loops around the world, highlighting the pros and cons of each facility with regard to reproducing and monitoring different multiphase flow situations. The authors suggest a way forward for new developments in this area.
Keywords: multiphase flow loop; multiphase flow modelling